The wage effects of social norms: evidence of deviations from peers' body-mass in Europe - René Fahr (Institute for the Study of Labor (IZA), 2006)
We investigate wage effects of deviations from peer group body mass index (BMI) to evaluate the influence of social norms on wages. Our approach allows for disentangling the influence of the social norm from any (anticipated) productivity effects associated with deviations from a clinically recommended BMI. Estimates of between effects models for 9 European countries for the years 1998-2001 suggest that the influence of the social norm varies considerably between countries and wage penalties are rather found for upward deviations from the norm and for men.
Keywords: 330